2008
DOI: 10.1590/s0037-86822008000400023
|View full text |Cite
|
Sign up to set email alerts
|

Detecção de sífilis por ensaios de ELISA e VDRL em doadores de sangue do Hemonúcleo de Guarapuava, Estado do Paraná

Abstract: O objetivo desse estudo foi avaliar a soroprevalência de sífilis em 5.752 doadores de sangue atendidos no Hemonúcleo de Guarapuava-PR, em 2006. As taxas de positividade foram de 2,1% pelo teste de ensaio imunoenzimático e 0,2% pelo Veneral Disease Research Laboratory, mostrando baixa prevalência de sífilis nos indivíduos que procuraram este banco de sangue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
2
2
1
8
Order By: Relevance
“…Similar results were found in towns of the same state; Cruz Alta (16) and Santa Maria (17) with prevalences of 0.3% and 0.48%, respectively. The positivity rate for the pathology in Guarapuava, Paraná (18) according to the immune enzyme test was 2.1%, thus a higher rate than that reported in the current study. Research in blood centers of other states also showed a high positivity rate for syphilis tests, such as those in the Brazilian states of Amazonas (19) , São Paulo (7) and Sergipe (20) .…”
Section: Discussioncontrasting
confidence: 77%
“…Similar results were found in towns of the same state; Cruz Alta (16) and Santa Maria (17) with prevalences of 0.3% and 0.48%, respectively. The positivity rate for the pathology in Guarapuava, Paraná (18) according to the immune enzyme test was 2.1%, thus a higher rate than that reported in the current study. Research in blood centers of other states also showed a high positivity rate for syphilis tests, such as those in the Brazilian states of Amazonas (19) , São Paulo (7) and Sergipe (20) .…”
Section: Discussioncontrasting
confidence: 77%
“…Furthermore, the statistical treatment of the non-responders to follow-up testing and of the independent variables (e.g., unknown residence and education level) in the multinomial regression analysis reduced the potential bias by providing estimates of the likely relative risk in these subgroups using a Poisson regression. The sociodemographic profi le of the present study is similar to other such profi les found in the Brazilian literature, reinforcing the validity of these results and allowing generalization to other areas of the country with similar profi les 8,11,15,22,27 . Additionally, this study provides useful elements for assessing the risk of syphilis transmission by blood transfusion and for improving hemovigilance.…”
Section: Ethical Considerationssupporting
confidence: 86%
“…A similar result was noted in the neighboring State of Parana, which reported a 0.2% prevalence in VDRL reactive donors 11 . However, the largest blood bank in the State of São Paulo had a 1.7% prevalence in 2007 6 .…”
Section: Ethical Considerationssupporting
confidence: 84%
See 1 more Smart Citation
“…In some countries, like Brazil, it is considered one of the major public health problems, similar to other emerging infectious diseases in the country. 20 According to the World Health Organization, it is estimated about 12 million new cases of people infected each year with some disease related to sex, among which syphilis has great representation. 21 Currently, the search for syphilis is done with specific and non-specific tests, and most laboratories have opted for Venereal Disease Research Laboratory (VDRL) and enzyme-linked immunosorbent assay (ELISA) for being easy to perform.…”
Section: Introductionmentioning
confidence: 99%